2022
DOI: 10.56499/jppres22.1489_10.6.1126
|View full text |Cite
|
Sign up to set email alerts
|

Molecular simulation of compounds from n-hexane fraction of Sonchus arvensis L. leaves as SARS-CoV-2 antiviral through inhibitor activity targeting strategic viral protein

Abstract: Context: COVID-19 was caused by the spread and transmission of SARS-CoV-2 at the end of 2019 until now. The problem comes when antiviral drugs have not yet been found and patients infected with SARS-CoV-2 can trigger a cytokine storm condition due to the effects of viral replication. Indonesia has various kinds of medicinal plants, such as Sonchus arvensis L., which are used as medicinal plants. Aims: To analyze the activity of the inhibitor as SARS-CoV-2 antiviral agents from n-hexane fractions of S. arvensis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 0 publications
0
17
0
Order By: Relevance
“…Predictions made with the Lipinski server showed that the metabolites (as ligands in this study) in the rhizome of C. sumatrana complied with Lipinski's rules, namely molecular weight (MW) < 500 Daltons, lipophilicity (LogP) < 5, hydrogen donor bond (HBD) <10, and molar refracticity (MR) 40-130. 19 These compounds are predicted to have good absorbivity and can trigger biological responses when interacting with target proteins.…”
Section: Resultsmentioning
confidence: 99%
“…Predictions made with the Lipinski server showed that the metabolites (as ligands in this study) in the rhizome of C. sumatrana complied with Lipinski's rules, namely molecular weight (MW) < 500 Daltons, lipophilicity (LogP) < 5, hydrogen donor bond (HBD) <10, and molar refracticity (MR) 40-130. 19 These compounds are predicted to have good absorbivity and can trigger biological responses when interacting with target proteins.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the docking results are visualized using the Biovia Discovery Studio Visualizer application version 21.1.1. Some of the parameters analyzed from the visualization results include bond energy, bond types, and amino acid residues 46,47,53 .…”
Section: Druglikeness Analysis and Admet Analysis Of Ligandsmentioning
confidence: 99%
“…14 The agent used also has a very strong effect which not only kills cancer cells but also attacks healthy cells, especially rapidly dividing cells. 15,52,53 chemotherapy companion agent in the management of breast cancer. The goal is to increase the sensitivity of cancer cells and reduce the side effects caused by chemotherapy agents.…”
Section: Introductionmentioning
confidence: 99%
“…21 Nonpolar molecules will gather to form aggregates in an aqueous environment which reduces entropy because water cannot form hydrogen bonds with nonpolar molecules. 25 The target of in-silico determination of drug compounds has a combination of hydrophobic interactions with one to three hydrogen bonds to increase the potential for stability in laboratory-scale testing. 23 The existence of electrostatic and van der Waals interactions can be useful in indicating the position of the binding site.…”
Section: Analysis Compounds and 3clpro Receptor Interactionmentioning
confidence: 99%
“…If two atoms with noncovalent bonds are close enough, then electrons from one atom will perturbate on the other atom producing a transient dipole that attracts the two atoms to each other. 25 The van der Waals interaction can predict the position of the binding site better with the presence of atoms at a certain distance which gives rise to an energy. 26 This interaction is needed by the body, especially for use as a drug molecule with the ability to bond back to its original state, that is, the compound and the receptor can combine to produce a response and eventually separate.…”
Section: Analysis Compounds and 3clpro Receptor Interactionmentioning
confidence: 99%